Pelayanan Administrasi Pertanahan di Kecamatan Jekan Raya Kota Palangka Raya: Land Administration Services in Jekan Raya District, Palangka Raya City - Irwani, Irwani; Andayani, Desi (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2018)
This study aims to examine and explain how the orderly implementation of land administration in the District of Jekan Raya, Palangka Raya City. The research method used is descriptive qualitative because the problems brought by researchers are still unclear in nature and are holistic (overall) sources of data in this study consisting of primary data and secondary data, which is the primary data is the Head of Government Section Land Registration, Officer land services, and communities that conduct land services in Jekan Raya Subdistrict, Palangka Raya City. Data collection techniques in this study are observation, interview, and documentation. Based on the results of the survey that the administrative service in the land is known to be still not optimal because service personnel are still often not on time in providing services, even lack of reliability of officers in delivering services, yet lack of facilities to support services, staff responsiveness in the service process is still limited in the service process in the service process there are still officers providing services with bitchy faces.